Penguatan Literasi Matematis Melalui Tips dan Trik Penyelesaian Soal PISA untuk Siswa SMK Assalam - Ucik Fitri Handayani; Qissiisiina Azzahro’ (Kilau Publishing, 2026)
This community service activity was conducted with the aim of improving students’ understanding and skills in solving problems based on the Programme for International Student Assessment (PISA). Mathematical literacy is one of the key competencies in education, particularly in addressing the challenges of national and international assessments. This activity was attended by 37 students from SMK Assalam using a participatory approach that included material presentations, discussions on problem-solving strategies, independent practice, as well as reflection and evaluation of learning outcomes. Pre-test and post-test evaluations showed an increase in participants’ average scores, reaching 85%. This indicates an improvement in their understanding and skills in solving problems based on real-life contexts. Additionally, feedback from participants indicated that the majority felt more confident and benefited from the problem-solving techniques provided in this workshop. However, several challenges were encountered during the activity, including students’ difficulty in understanding context-based problems and time management issues while working on the problems. Therefore, for similar activities in the future, it is recommended that there be further mentoring, more intensive practice with problems, and a group-discussion-based approach to optimize understanding. Overall, this workshop made a positive contribution to improving students’ mathematical literacy and can serve as a model for schools in developing more applied and problem-solving-based learning.